2015
DOI: 10.1161/circheartfailure.114.001711
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Factor Gene Transfer Improves Cardiac Function After Myocardial Infarction in Swine

Abstract: Background Stem cell factor (SCF), a ligand of the c-kit receptor, is a critical cytokine which contributes to cell migration, proliferation, and survival. It has been shown that SCF expression increases after myocardial infarction (MI) and may be involved in cardiac repair. The aim of this study was to determine whether gene transfer of membrane-bound human SCF improves cardiac function in a large animal model of MI. Methods and Results A transmural MI was created by implanting an embolic coil in the left a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…These data are consistent with previously published reports using a similar approach to induce ischemic HF. 13,15 At 2 weeks after MI, coronary angiograms revealed TIMI 2 flow in 8 animals and TIMI 3 flow in 2 animals (1 each in Impella and SNP groups) in the LAD.…”
Section: Discussionmentioning
confidence: 99%
“…These data are consistent with previously published reports using a similar approach to induce ischemic HF. 13,15 At 2 weeks after MI, coronary angiograms revealed TIMI 2 flow in 8 animals and TIMI 3 flow in 2 animals (1 each in Impella and SNP groups) in the LAD.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous reports 23, 37 , but also due to the white-spotting phenotype that is often produced from mutations in the cKit and SCF loci, we expected that the SCF/cKit signaling pathway would affect CSCs mobilization by MSCs. However, we did not find evidence that modulation of SCF/cKit is sufficient to control CSC mobilization.…”
Section: Discussionmentioning
confidence: 99%
“…SCF is the ligand for c-kit, a receptor expressed by many types of SC [1]. Moreover, local injection of SCF, as well as cardiomyocyte-specific overexpression of SCF, has improved cardiac function after MI in mice [10,29,30]. A number of studies have reported evidence for cardiomyocyte renewal in the adult mammalian heart [3,27,28], but their origin, rate of turnover and physiological significance remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Stem cell factor plays a critical role in regulating the maintenance and expansion of hematopoietic SC in the BM where it is expressed by stromal cells and released through the action of matrix metalloproteinase 9 (MMP-9) [4][5][6]. Adult c-kit-positive cardiac SC are required for regeneration and repair in mouse models of myocardial damage [9], and SCF gene transfer has been shown to improve cardiac function after myocardial infarction (MI) in swine [10]. Adult c-kit-positive cardiac SC are required for regeneration and repair in mouse models of myocardial damage [9], and SCF gene transfer has been shown to improve cardiac function after myocardial infarction (MI) in swine [10].…”
Section: Introductionmentioning
confidence: 99%